The Adverse Cardiovascular Effects and Cardiotoxicity of Kratom (Mitragyna speciosa Korth.): A Comprehensive Review - Leong Bin Abdullah, Mohammad Farris Iman; Singh, Darshan (Frontiers in Pharmacology, 2021)
Background: Kratom or Mitragyna speciosa (Korth.) has received overwhelming attention recently due to its alleged pain-relieving effects. Despite its potential therapeutic value, kratom use has been linked to many occurrences of multiorgan toxicity and cardiotoxicity. Accordingly, the current narrative review aimed to provide a detailed account of kratom’s adverse cardiovascular effects and cardiotoxicity risk, based on in vitro studies, poison center reports, coroner and autopsy reports, clinical case reports, and clinical studies. Methods: An electronic search was conducted to identify all research articles published in English from 1950 to 2021 using the major research databases, such as Google Scholar, Web of Science, PubMed, Scopus, Mendeley, EMBASE, Cochrane Library, and Medline. We then analyzed the literature’s discussion of adverse cardiovascular effects, toxicity, and mortality related to kratom use. Results: Our findings revealed that, although in vitro studies have found kratom preparations’ most abundant alkaloid—mitragynine—to cause a prolonged QTc interval and an increased risk of torsades de pointes, a clinical study examining humans’ regular consumption of kratom did not report such a risk. However, this latter study did show that regular kratom use could induce an increased QTc interval in a dose-dependent manner. A few case reports also highlighted that kratom consumption is associated with ventricular arrhythmia and cardiopulmonary arrest, but this association could have ensued when kratom was co-administered with another substance. Similarly, analyses of national poison data showed that kratom’s most common adverse acute cardiovascular effects include tachycardia and hypertension. Meanwhile, coroner and autopsy reports indicated that kratom’s cardiovascular sequelae encompass coronary atherosclerosis, myocardial infarction, hypertensive cardiovascular disease, left ventricular hypertrophy, cardiac arrhythmia, cardiomegaly, cardiomyopathy, focal band necrosis in the myocardium, and myocarditis. Given the available data, we deduced that all cardiac eventualities reported in the literature could have been compounded by polysubstance use and unresolved underlying medical illnesses. Conclusion: Although kratom use has been associated with death and cardiotoxicity, especially at higher doses and when associated with other psychoactive drugs, the dearth of data and methodological limitations reported in existing studies do not allow a definitive conclusion, and further studies are still necessary to address this issue.